Le sort des « lumumbistes » chiliens face aux enjeux de la guerre froide (1964-1973) - Rafael Pedemonte (Caravelle)
Chilean students at the Patrice Lumumba University were the most important Chilean community in a foreign institution, thus becoming a symbol of the good relations with Moscow during Frei’s administration after 1964. Nevertheless, worried about the real intentions behind the granting of the scholarships delivered by the Soviets, the authorities got suspicious. However, living in the USSR provided a rich experience for these students who, back in their country, finally succeed in integrating into Chilean professional circles, at least until Pinochet’s coup d’état in 1973.